The analysis of health condition and the assessment of the risk of neoplastic diseases among residents of villages - Lewandowska, Anna; Lewandowski, Tomasz; Laskowska, Barbara (Journal of Education, Health and Sport, 2017)
Introduction: Neoplastic diseases have been classified as civilization diseases and are a big problem for modern medicine. According to the data from the International Agency for Research of Cancer, about 10 million people suffer from cancer and a number of deaths due to this disease has exceeded 6 million; until 2020 those numbers may double. In Poland, cancer survivors of five years concern 22% of men and 35% of women suffering from tumours, while in northern and western Europe there is a cure rate of 40% for men and 50% for women. The main reason for the adverse situation in Poland is a low percentage of early diagnosis of cancer. On the one hand this results from insufficient preparation of both family doctors and physicians of other specialties, but on the other, from insufficient dissemination of early diagnosis methods. Objective: The objective of the study is to analyze the health condition and to assess the risk of a neoplastic disease among residents of villages. Material and methods: The research involved 1000 residents of villages in Podkarpackie Voivodeship. The age of the researched ranges from 18 to 30 years, with mean age 26.96±0.84 (range [18;30], median 25.95%CI [18,9;29,01]). The researched group is represented in 43,8% by women in 56,2% by men. In order to obtain the research material, a standardized questionnaire has been applied including interview and physical examination, enabling assessment of symptoms reported during the interview and analysis of symptoms indicating a disease, including cancer. Results: According to the data analysis, during last few months the respondents have suffered from such ailments as cough (8.22% W, 7.12% M), dyspnea (3.2% W, 1.78% M), abdominal pain (13.7% W, 4.27% M), pain (5.48% W, 2.14% M) and weakness (14.61% W, 4.98% M). During observations, one female respondent was diagnosed with symptoms of melanoma (0.46%), which has been confirmed in later dermatological test. Conclusions: No changes in oral cavity suggesting neoplastic disease have been noticed. Every sixth respondent has enlarged lymph nodes, most frequently submandibular or neck’s lymph nodes, and in the majority of cases it’s accompanied by pain.